Institutional Investor Attention and Firm Disclosure - Abramova, Inna; Core, John E.; Sutherland, Andrew (The Accounting Review, 2020)
ABSTRACT We study how short-term changes in institutional owner attention affect managers' disclosure choices. Holding institutional ownership constant and controlling for industry-quarter effects, we find that managers respond to attention by increasing the number of forecasts and 8-K filings. Rather than alter the decision of whether to forecast or to provide more informative disclosures, attention causes minor disclosure adjustments. This variation in disclosure is primarily driven by passive investors. Although attention explains significant variation in the quantity of disclosure, we find little change in abnormal volume and volatility, the bid-ask spread, or depth. Overall, our evidence suggests that management responds to temporary institutional investor attention by making disclosures that have little effect on information quality or liquidity. JEL Classifications: G23; G32; G34; G12; G14.